Neoformation of soil aggregates after a volcano eruption in meadows of Northern Patagonia, Argentina - Enriquez, Andrea Soledad; Cremona, Maria Victoria; Peri, Pablo Luis; Six, Johan (2018)
In June 2011, a natural event occurred in Patagonia, Argentina: The “Puyehue-Cordón Caulle” volcanic complex erupted, and particles from tephras (1-5cm) to very fine volcanic ash (44-500?m) where deposited in the direction of prevailing winds (West to East). The ash was biologically inert, with no organic compounds, neutral pH and low electrical conductivity. The objective was to study neoformation processes of soil aggregates in wet meadows after volcano eruption